The Ashgate research companion to modern warfare - Kassimeris, George; Buckley, John (John D.) (Ashgate research companion, 2010)
This research collection provides a comprehensive study of important strategic, cultural, ethical and philosophical aspects of modern warfare. It offers an analysis of key issues in modern warfare, not only in terms of the conduct of war and the wider complexities and ramifications of modern conflict, but also concepts of war, the crucial shifts in the structure of warfare, and the morality and legality of the use of force in a post-9/11 age